Studies in the History of Russian-Israeli Literature - Shrayer, Maxim D. (Academic Studies Press, 2023)
This collection of essays covers a hundred-year history of Russian-language literature in Israel, including the pre-state period. Some of the studies are devoted to an overview of the literary process and the activities of its participants, others-to individual genres and movements. As a result, a complex and multifaceted picture emerges of a not quite fully defined, but very lively and dynamic community that develops in the most difficult conditions. The contributors trace the paths of Russian-Israeli prose, poetry and drama, various waves of avant-garde, fantasy, and critical thought. Today, in Russian-Israeli literature, the voices of writers of various generations and waves of repatriation are intertwined: from the "seventies" to the "war aliyah" of the recent times. Both the Russian-Israeli authors and their critics often hold different opinions of their respective roles in Israel's historical and literary storms. While disagreeing on the definition of their place on the map of modern culture, Russian-Israeli writers are united by a shared bond with the fate of the Jewish state.